Happiness and its influencing factors among paddy farmers in Granary Area of Mada - Kamarudin, Roslina; Ali, Jamal; Mohd Saad, Nariman (International digital organization for scientific information (IDOSI), 2013)
The study aims to study the factors associated with the level of happiness among paddy farmer’s household in the granary area of Kedah. The study used quantitative research technique by using interview questionnaire to obtain data at the household level.Structural Equation Modeling (SEM) used to analyze the factors affecting happiness of the paddy farmers statistically.The study found that the institution factor is the most significant factor contributing to happiness of paddy farmer’s household with the coefficient value of 0.36. The finding shows that the role played by MADA, particularly in terms of advisory assistance to farmers have succeeded to improve happiness of farmers in the area.The management of leisure time, ownership of financial assets and human assets also positively significant influencing the happiness of paddy farmers.In addition the environment factors such as pollution, land degradation and waste disposal also significant influencing happiness of paddy farmers negatively. Finding also suggests that farm management factor indicated by variables such as effective use of machinery, pest control and weed control are not able to increase the happiness of paddy farmers.This situation clearly shows that the increase in cultivation technology with the usage of mechanization in every production process and harvesting is not able to increase the happiness of paddy farmers especially the poor.Thus, active involvement from related institution, strengthening the financial and human assets, as well as the introduction of technology that is more acceptable to the farmers, seen are the best way to raise the level of happiness among the paddy farmers.